Religious Harmony: Epitome For Global Peace - Khalil- ur- Rahman , Dr. Badshah Rahman , Dr. Asad Ullah (Migration Letters, 2024)
The world is a religious, diverse global village. It is the dire need of today to promote religious harmony among the different religions to establish global peace. Religious harmony fosters a multi-religious society by ensuring unity and respect among the different followers. Religious diversity and religious prejudices are considered significant factors that promote conflicts and violence all over the world. Although every religion emphasizes unity and respect for humanity, No religion teaches against a man to a man. Still, the religious prejudices of followers are the principal source of destroying a peaceful environment. This study aimed to explore different religions’ views regarding religious harmony and global peace. This study was qualitative in nature and focused on secondary data. Data was collected through sacred books, research articles, and online resources. Six major religions, i.e., Judaism, Christianity, Islam, Hinduism, Sikhism, and Buddhism, were selected for research. The main research question was: What is the role of religion in promoting religious harmony and global peace? The study’s findings show that each religion’s teachings emphasize peace, harmony, tolerance, and respect for other religions and beliefs. Based on the findings of the study, it is recommended to promote religious harmony to establish global peace.